Kelayakan Hair Tonic Daun Pare (Momordica Charantia L) Untuk Perawatan Rambut Rontok - Safitri, Mayang; Novelni, Ringga (Jurnal Tata Rias, 2024)
Bitter melon leaves (Momordica Charantia L) can be used as the main ingredient in a hair tonic because they contain flavonoids and vitamin C, which can help overcome hair loss. The objectives of this study are to a) find out how to make bitter melon leaves as a hair tonic, b) to find out the feasibility of bitter melon leaf hair tonic seen from the chemical content such as flavonoids and vitamin C, c) to find out the feasibility of hair tonic seen from the evaluation of preparations such as organoleptic and pH tests, d) to find out the feasibility of hair tonic seen from the hedonic test (panelists' preference for bitter melon leaf hair tonic), e) to find out the feasibility of bitter melon leaves as a hair tonic. This type of research is quantitative descriptive research. The tests for flavonoid and vitamin C content and pH were conducted at the FMIPA UNP Laboratory and the Pharmacy Laboratory of Perintis Indonesia University. The research targets bitter melon leaves, which are processed into a hair tonic to address hair loss. The feasibility of Bitter Melon Leaves as a hair tonic is assessed through laboratory, organoleptic, and hedonic tests. Up to 7 people in the discussion room. The data analysis technique uses descriptive analysis by showing the percentage. In this study, based on the research results obtained, bitter melon leaf preparations were made in liquid form. The flavonoid content of bitter melon leaves was 16 mg / 100 g (1.63%), and Vitamin C was 33.24%. Based on the organoleptic test, the odor indicator scored 71% in the distinctive bitter melon leaf smell category, the color indicator scored 71% in the dark brown category, and the absorption indicator scored 71% in the sufficient absorption category. The feasibility of bitter melon leaf hair tonic was determined by the results of the hedonic test (panelists' preferences), which showed a value of 57% in the like category. The researcher hopes that the results of this study on the suitability of bitter melon leaf hair tonic for hair loss can serve as a reference for further research and refinement in the cosmetology and beauty department.